PARTISIPASI MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH WALIKOTA DAN WAKIL WALIKOTA BEKASI TAHUN 2012 - Vidya Nurrul Fathia; Kushandayani .; Fitriyah . (Journal of Politic and Government Studies, 2015)
ABSTRACTThis study aims to concern about issues related to participation of Bekasi citizen in 2012 election of bekasi mayor and vice mayor. Based on data, Bekasi citizen gave a small number in voting. The study aims to investigate the cause of this issue. The study was conducted with qualitative methods to explain factors related to low voter participation in Bekasi city’s mayor and vice mayor election. Analysis of this study was combined primary and secondary data alon with interview to 20 informants. The results showed that the election was being held during the time when voters as they chose not vote, second factor is the mayor and vice mayor aren’t reliable candidates based on voter’s expectation. The last factor is many voter in Bekasi was disappointed with the previous mayor. Some voters become apathetic as the resuly of previous selection. My research suggests that increasing voters’s participation is not only related to the comitee of the election task but also needs more attention and concerns from the local government and society in the areit self as the main point of this event.The key word:Citizen’s participation, Head of district’s election